Effect of Baby Massage on Baby’s Sleep Quality (Based on Baby Massage Duration and Frequency) - Darah Ifalahma; Lutfia Rahma Dwi Cahyani (LPPM Universitas Duta Bangsa Surakarta, 2019)
Baby’s sleep quality gives an influence on baby growth and development. One problem mothers often encounter is that their babies have trouble falling asleep. One of efforts to improve baby’s sleep quality and quantity is giving a massage. Massage can stimulate the production of endorphins, making possible to relieve pain, and thereby causing babies to calm down and their crying frequency to reduce. The present research seeks to find out the effectiveness of baby massage to improve baby’s sleep quality viewed from baby massage duration and frequency. A quasi-experimental design was applied in the research. The independent variable includes baby massage therapy, the dependent variable covers baby’s sleep quality. The research samples are 3-6 month old babies. The analysis was carried out in two stages. Phase I is the normality test using the Kolmogorov Smirnov method and homogeneity test using the Levene's test method. Phase II is the Influence Test used is Two Way Anava. There is an actual difference of influence between a baby group given 15 minute massage and that given 30 minute massage (p=0.041<0.05); there is a difference in baby’s sleep quality based on massage frequency in a week (once, three times, and six times) with p=0.005<0.05 and there is a significant interaction between massage duration and frequency towards baby’s sleep quality (p=0.001<0.05). Baby massage was effective to improve the quality of baby sleep. Baby massage that is getting more frequent and long, can improve the quality of baby's sleep better.